Film art : an introduction - Bordwell, David; Thompson, Kristin, 1950- (New York McGraw Hill, 2017)
"Studying the arts isn't only about learning facts and concepts either, although both are important. In addition, studying the arts broadens our tastes. In eleven editions of Film Art, we've made reference to many well-known films but also to many that you've probably never heard of. This is part of our plan.We want to show that the world of cinema teems with a great many unexpected pleasures, and we hope to get you curious"--
Machine generated contents note: -- Part 1 Film Art and Filmmaking -- 1. Film as Art: Creativity, Technology, and Business -- Part 2 Film Form -- 2. The Significance of Film Form -- 3. Narrative Form -- Part 3 Film Style -- 4. The Shot: Mise-en-Scene -- 5. The Shot: Cinematography -- 6. The Relation of Shot to Shot: Editing -- 7. Sound in the Cinema -- 8. Summary: Style as a Formal System -- Part 4 Types of Films -- 9. Film Genres -- 10. Documentary, Experimental, and Animated Films -- Part 5 Critical Analysis of Films -- 11. Film Criticism: Sample Analyses -- Appendix: Writing a Critical Analysis of a Film -- Part 6 Film History -- 12. Historical Changes in Film Art: Conventions and Choices, Tradition and Trends -- Glossary -- Credits -- Recommended DVD and Blu-Ray Supplements.
Includes bibliographical references and index.
Keywords: Motion pictures -- Aesthetics; PERFORMING ARTS / Film & Video / General